Mitochondrial Dysfunction in Diabetes: Shedding Light on a Widespread Oversight - Franklyn Nonso Iheagwam; Amarachi Joy Joseph; Eniola Deborah Adedoyin; Olawumi Toyin Iheagwam; Samuel Akpoyowvare Ejoh (Pathophysiology)
Diabetes mellitus represents a complicated metabolic condition marked by ongoing hyperglycemia arising from impaired insulin secretion, inadequate insulin action, or a combination of both. Mitochondrial dysfunction has emerged as a significant contributor to the aetiology of diabetes, affecting various metabolic processes critical for glucose homeostasis. This review aims to elucidate the complex link between mitochondrial dysfunction and diabetes, covering the spectrum of diabetes types, the role of mitochondria in insulin resistance, highlighting pathophysiological mechanisms, mitochondrial DNA damage, and altered mitochondrial biogenesis and dynamics. Additionally, it discusses the clinical implications and complications of mitochondrial dysfunction in diabetes and its complications, diagnostic approaches for assessing mitochondrial function in diabetics, therapeutic strategies, future directions, and research opportunities.